Pengaruh Kualitas Produk, Brand Image dan Promosi terhadap Kepuasan Pelanggan melalui Keputusan Pembelian Produk Kongbap - Nursah, Muchamad; Wahid Akbar Basudani (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
The objective of this investigation is to examine the influence of product quality, promotion, and brand image upon purchase decisions and the resulting consequence for customer satisfaction regarding Kongbap products. This investigation utilized a descriptive method with a quantitative design, wherein information was gathered via surveys administered to consumers of Kongbap within the DKI Jakarta region. The examination of data was executed with SmartPLS version 4, applying the Structural Equation Modeling (SEM) methodology. The findings indicate that product quality and brand image exert a substantial and favorable influence on purchase decisions, whereas promotion lacks a potent direct influence. Purchase decisions serve a critical function in enhancing customer satisfaction. Additionally, purchase decisions function as a successful intermediary in the connection linking product quality and brand image to customer satisfaction, demonstrating respective indirect effect magnitudes of 0.2114 and 0.2205. The conclusion of this study emphasizes that an integrated strategy focusing on improving product quality and strengthening brand image needs to be consistently implemented to encourage purchase decisions and create customer satisfaction in healthy food products such as Kongbap.